2008
DOI: 10.1159/000182420
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Compensatory Neural Recruitment in Aging and Risk for Alzheimer’s Disease: Review and Recommendations

Abstract: There has been a recent proliferation of functional magnetic resonance imaging (fMRI) studies that interpret between-group or within-group differences in brain response patterns as evidence for compensatory neural recruitment. However, it is currently a challenge to determine whether these observed differences are truly attributable to compensatory neural recruitment or whether they are indicative of some other cognitive or physiological process. Therefore, the need for a standardized set of criteria for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 112 publications
7
39
0
1
Order By: Relevance
“…2b) [4]. Hypoconnectivity within DMN is possibly due to early amyloid deposition in regions with high metabolism (posterior cingulate-precuneus complex within the DMN) [13,14]. Reduced rsFC within DMN is observed in patients with presymptomatic AD (mild cognitive impairment) and cognitively normal elders with amyloid deposition [15,16,17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b) [4]. Hypoconnectivity within DMN is possibly due to early amyloid deposition in regions with high metabolism (posterior cingulate-precuneus complex within the DMN) [13,14]. Reduced rsFC within DMN is observed in patients with presymptomatic AD (mild cognitive impairment) and cognitively normal elders with amyloid deposition [15,16,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced rsFC within DMN is observed in patients with presymptomatic AD (mild cognitive impairment) and cognitively normal elders with amyloid deposition [15,16,17,18]. As rsFC of DMN is correlated with cognitive functions, DMN hypoconnectivity may reflect the core pathophysiology underlying verbal memory deficits in AD [15,16,18], while hyperconnectivity within the EN is attributed to compensatory mechanisms secondary to primary hypoconnectivity [13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…One group (Bondi et al 2005;Han et al 2007Han et al , 2008 has proposed that the increased activation observed in asymptomatic carriers of the APOE e4 allele represents compensatory recruitment. They propose that the compensatory mechanism includes recruitment of additional brain regions and different patterns of activation in order to maintain or improve cognitive performance.…”
Section: Cross-sectional Fmri Studies Of Risk Of Cognitive Declinementioning
confidence: 99%
“…They propose that the compensatory mechanism includes recruitment of additional brain regions and different patterns of activation in order to maintain or improve cognitive performance. This RegionActivation-Performance model (Han et al 2008) infers that the function of the increased signal is to combat cognitive impairment in the presence of declining neural resources, and may be indicative of an increased risk for subsequent cognitive decline. Perhaps the early, more intensive, and possibly less efficient utilization of these neural structures by APOE e4 carriers may make them more susceptible to later degeneration and AD neuropathology.…”
Section: Cross-sectional Fmri Studies Of Risk Of Cognitive Declinementioning
confidence: 99%
See 1 more Smart Citation